Cost-effectiveness of entecavir versus lamivudine for the suppression of viral replication in chronic hepatitis B Patients in Brazil - Costa,Anna Maria N. (2008)
Hepatitis B virus infection is an important public-health issue. Chronic patients have a higher risk of death due to complications, which increases health-care expenses in. Cost-effectiveness analysis of entecavir (ETV) versus lamivudine (LVD) for treatment of chronic hepatitis B, in e antigen (AgHBe)-positive and negative patients, based on two phase 3, controlled and randomized studies. A decision analysis model was developed, using the following endpoints: cost per patient with undetectable viral load and cost per quality life year (QALY) gained. Risks for complications (compensated or decompensated cirrhosis and hepatocellular carcinoma) were based on the cohort study REVEAL, published in 2006. The REVEAL parameters were applied to the results of the viral load levels obtained from the clinical assay data. The complication costs were based on a study of the disease cost conducted in Brazil, in 2005. The cost data were obtained predominantly from Sistema Único de Saúde [SUS - Brazilian public health system] payment tables and drug price lists. The utility data were obtained from literature and life expectancy information was based on IBGE data. The analysis perspective was that of SUS. A discount rate of 3% per year was used. For the horizon of time of 10 years, the ETV had an incremental cost of approximately two million Brazilian Reais (R$) compared to LVD. Reducing the number of complications, ETV treatment reduced costs by around 3 million, reducing final costs by 1 million, for AgHBe-positive patients. ETV also reduced the incremental cost per QALY gained. ETV was found to be the most cost-effective alternative for AgHBe-positive and negative patients.